2016
DOI: 10.18632/oncotarget.7985
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatase of regenerating liver-3 inhibits invasiveness and proliferation in non-small cell lung cancer by regulating the epithelial-mesenchymal transition

Abstract: Phosphatase of regenerating liver-3 (PRL-3) has been reported to be associated with colon and gastric cancer metastasis. However, the role and function of PRL-3 in human non-small cell lung cancer cells is unknown. Our studies showed that the expression of PRL-3mRNA and protein are higher in less invasive human lung adenocarcinoma cells than in highly invasive cell lines. Ectopic expression of PRL-3 reduced cell capacity for anchorage-dependent growth, anchorage-independent growth, migration, and invasion in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Previous studies highlighted EMT as the mechanism by which differentiated epithelial cells undergo notable morphological alterations and acquire more motile and invasive capabilities ( 16 19 ). Cytoskeletal reorganization is also a characteristic of EMT and this feature was observed by F-actin staining.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies highlighted EMT as the mechanism by which differentiated epithelial cells undergo notable morphological alterations and acquire more motile and invasive capabilities ( 16 19 ). Cytoskeletal reorganization is also a characteristic of EMT and this feature was observed by F-actin staining.…”
Section: Resultsmentioning
confidence: 99%
“…It illustrates a possible relationship between drug resistance and invasive potential, as further confirmed by our results. Accumulating evidence has highlighted EMT as the mechanism by which differentiated epithelial cells undergo remarkable morphological changes and acquire more motile and invasive capabilities [29][30][31][32] . Here, we found that A549/ DDP and A549/TAX cells were spindle-shaped and exhibited reduced cell contact ( Figure 3A).…”
Section: Cisplatin or Paclitaxel-resistant A549 Cells Exhibit An Emt-mentioning
confidence: 99%
“…12,13 Slug, which is also known as SNAI2, is a transcription factor that is involved in regulation of ECM in GC. 14,15 In this study, we found that P4HA3 is significantly upregulated in GC than in normal tissues, and its upregulation is epigenetically activated by Slug. Also, we also observed that P4HA3 upregulation is associated with GC metastasis and poor survival.…”
Section: Introductionmentioning
confidence: 51%